2018
DOI: 10.1103/physrevfluids.3.063201
|View full text |Cite
|
Sign up to set email alerts
|

Role of hydrodynamic shear layer stability in driving combustion instability in a premixed propane-air backward-facing step combustor

Abstract: This paper presents a global hydrodynamic stability analysis of flow fields in a backwardfacing step combustor, assuming weakly nonparallel flow. The baseline experiments in a "long" combustor of length of 5.0 m shows the presence of two combustion instability states characterized by coherent low-and high-amplitude acoustic pressure oscillations. The analysis is performed for propane-air mixtures at three values of φ = 0.63, 0.72, and 0.85, which correspond to quiet, low-amplitude and high-amplitude instabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…13a and 13b with Figs. 5 and 7 would immediately reveal, disturbances are now located essentially in the right portion of the cavity and there is strong evidence for their essentially vertical-shear-driven nature (the interested reader being also referred to the similar studies recently carried out by Ali and Dey [78] and Hemchandra et al [79]). After discussing in the previous section the dynamics of hybrid forced-buoyancy convection as a result of cold fluid injection through an inflow section located on top of the left sidewall, we finally address the case for which the inflow section is positioned relatively close to the floor.…”
Section: Cross Comparison Of Table V With Tablementioning
confidence: 64%
“…13a and 13b with Figs. 5 and 7 would immediately reveal, disturbances are now located essentially in the right portion of the cavity and there is strong evidence for their essentially vertical-shear-driven nature (the interested reader being also referred to the similar studies recently carried out by Ali and Dey [78] and Hemchandra et al [79]). After discussing in the previous section the dynamics of hybrid forced-buoyancy convection as a result of cold fluid injection through an inflow section located on top of the left sidewall, we finally address the case for which the inflow section is positioned relatively close to the floor.…”
Section: Cross Comparison Of Table V With Tablementioning
confidence: 64%
“…The results showed the FTF to be very sensitive especially to variations of the flame speed and the inlet duct temperature. Hemchandra et al 12 analyzed the role of hydrodynamic shear layer instabilities for CI. They found that acoustic-hydrodynamic coupling can lead to CI by closed and semi-open loop mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Hemchandra et al. 12 analyzed the role of hydrodynamic shear layer instabilities for CI. They found that acoustic-hydrodynamic coupling can lead to CI by closed and semi-open loop mechanisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that the primary driving mechanism of 1k Hz combustion instability is the acoustically coupled pulsating motion of the inner H 2 /O 2 flame or periodic ignition of H 2 /O 2 mixture. Recently, Hemchandra et al 11 discovered that there are two different mechanisms driving combustion instability. One is a strong coupling between acoustics and hydrodynamic modes.…”
mentioning
confidence: 99%